THE COMMODIFICATION OF RELIGION IN AINIQUA MINERAL WATER PRODUCTS IN MEDAN CITY - Muhammad Safitrah; Muhammad Jailani (Journal Analytica Islamica, 2026)
The phenomenon of religious commodification in consumer products is increasingly evident through the use of religious symbols, narratives, and identities as marketing strategies. This study aims to analyze the process of religious commodification in Ainiqua mineral water products in Medan City and identify factors that hinder its implementation. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of four people, consisting of Ainiqua managers, production heads/workers, religious leaders, and consumers in Medan City. The analysis was conducted by referring to Vincent Mosco's commodification theory and Theodor Adorno's cultural industry theory. The results show that religious commodification in Ainiqua products occurs through three main forms. First, content commodification is seen in the use of the "prayer water" narrative, murottal chanting, halal labels, and hijaiyah letter symbols as added value to the product. Second, audience commodification is carried out by targeting the Muslim middle class and the da'wah community as a market base. Third, labor commodification is seen in the involvement of workers who interpret production activities as part of spiritual devotion. This research also identified several obstacles, such as competition in the mineral water market, resistance from some communities to the commercialization of religious symbols, and the challenge of maintaining a balance between spiritual values and economic interests. This research contributes to enriching studies of religious communication, the political economy of communication, and the halal industry by demonstrating how religious symbols are constructed into economic value in the marketing practices of everyday consumer products.